IMPRESSION OF NON-PERFORMING LOAN, LOAN TO DEPOSIT RATIO, AND NET INTEREST MARGIN AGAINST PROFITABILITY - Miryam Alawiyah; Dedy Wijaya Kusuma; Fetri Setyo Liyundira (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2020)
This study aims to determine the effect of Net Performing Loans, Loan to Deposit Ratio, and Net Interest Margin on profitability. Profitability is proxied by Return On Assets (ROA). Whereas the factor for the existence of Net Performing Loans (NPL) is proxied by non-performing loans, the Loan to Deposit Ratio (LDR) factor is proxied by third-party fund distribution, and the Net Interest Margin (NIM) factor is net interest income proxied. The population in this study amounted to 25 Rural Banks (BPR) in the Jember Regency, and for the study, the sample was 19 People's Credit Banks (BPR) in the Jember Regency, which were selected using the purposive sampling method for the 2017-2018 period. Data were analyzed using multiple linear regression. Based on the test results, it was concluded that the components of the Net Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) affect the profitability using the Return on Assets (ROA) ratio. This proves that Non-Performing Loans (NPLs), Loans to Deposit Ratio (LDR), and Net Interest Margin (NIM) can be used to measure how much income the Bank earns.